Irradiation of D-3He fuel by d-beam to enhance fusion energy gain via ICF using innovative whistler wave collapse by MCNPX simulation - Hosseinimotlagh, S.N. (Recent Contributions to Physics, 2024)
In this article, we used as another new method to achieve higher fusion energy gain. In this approach, the ultimate goal is to heat the ions to a large amount of temperature to enhance the number of nuclear reactions. In the design of laser fusion, as much as possible, it is necessary to convert the laser energy into the energy of fuel ions by various types of laser-plasma interactions. But the main problem is that the electrons absorb a lot of laser energy in the first phase of interaction. The transfer of energy from electron to ion through collisional processes happens slowly and is not very efficient. Thus, the matter of transferring energy directly from electromagnetic waves to ions can overcome this basic problem. Therefore, the aim of this research is to investigate the effective mechanism of energy transfer directly from the laser to the super dense ions of D3He fuel due to the collapse of standing whistler waves (SWW). In this article, through the numerical solution of coupled point nonlinear kinetic differential equations governing this fuel, taking into account the effect of the collapse of whistler waves, we obtained the desired fuel energy gain of approximately 74 using D-beam along whistler standing waves collapse via MCNPX simulation, which is compared to the mode of without considering these electromagnetic waves is a high gain.